Effect of aprepitant on kynurenine to tryptophan ratio in cART treated and cART naïve adults living with HIV. Issue 23 (11th June 2021) - Spitsin, Sergei; Pappa, Vasiliki; Kinder, Annemarie; Evans, Dwight L.; Rappaport, Jay; Douglas, Steven D.
Abstract : Abstract: Changes in tryptophan metabolism affect human physiology including the immune system, mood, and sleep and are associated with human immunodeficiency virus (HIV) pathogenesis. This study investigates whether the treatment of HIV-infected individuals with the neurokinin-1 receptor antagonist, aprepitant, alters tryptophan metabolism. This study utilized archival samples from 3 phase 1B clinical trials "Anti-HIV Neuroimmunomodulatory Therapy with Neurokinin-1 Antagonist Aprepitant"-2 double-blinded, placebo-controlled, and 1 open-label study. We tested samples from a total of 57 individuals: 26 combination antiretroviral therapy (cART) naïve individuals receiving aprepitant, 19 cART naïve individuals receiving placebo, and 12 individuals on a ritonavir-containing cART regimen receiving aprepitant. We evaluated the effect of aprepitant on tryptophan metabolism by measuring levels of kynurenine and tryptophan in archival plasma samples and calculating the kynurenine to tryptophan ratio. Aprepitant treatment affected tryptophan metabolism in both cART treated and cART naïve individuals with more profound effects in patients receiving cART. While aprepitant treatment affected tryptophan metabolism in all HIV-infected patients, it only significantly decreased kynurenine to tryptophan ratio in cART treated individuals. Aprepitant treatment offers an opportunity to target inflammation and mood disorders frequently co-existing in chronic HIV infection.